Complete Corpus Callosum Agenesis: Can It Be Mild?. (29th August 2012) - Chiappedi, Matteo; Fresca, Anna; Baschenis, Ilaria Maria Carlotta
Abstract : Corpus callosum agenesis is a relatively common brain malformation. It can be isolated or included in a complex alteration of brain (or sometimes even whole body) morphology. Etiology and pathogenetic mechanisms have been better understood in recent years due to the availability of more adequate animal models and the relevant progresses in developmental neurosciences. We present the case of a girl with a complete agenesis of the corpus callosum discovered at birth. She had mild learning difficulties, but reached satisfactory levels of autonomy after an individually tailored rehabilitative treatment. Her story is discussed in light of recent findings, which emphasize the possibility to exploit brain plasticity and the utility of an individually tailored approach, defined on the basis of a dialogue with the family and the patient.